Global Trends in Cryptocurrency Accounting Research: A Bibliometric Analysis of Scopus Publications (2015–2025) - Loso Judijanto; Reni Anggraeni; Andry Irdyansah; Ahalik Ahalik; Muhamad Rizky Wijaya; Eko Sudarmanto (Westscience Press, 2026)
The unprecedented development of cryptocurrencies and blockchain technologies has posed major challenges to traditional accounting standards and procedures. As a result, there is a rising number of scholarly contributions to this topic. The goal of this paper is to explore global trends in cryptocurrency accounting research from the perspective of bibliometrics based on the papers published in Scopus databases between 2015 and 2025. Data was gathered systematically and analyzed using VOSviewer software to visualize and interpret co-authorship networks, citation structures, and keyword co-occurrence clusters. Cryptocurrency and blockchain emerge as the key concepts of all research streams, such as financial reporting, auditing, regulation, and fintech. It can be stated that there is an unevenly distributed global collaboration network in which countries like the US, China, and India are leading. There is also a tendency towards a growing interest in applied aspects related to financial markets, risks management, and regulations. The field seems to mature in terms of research and practical applications. However, the current state of affairs implies some research gaps concerning accounting standardization, IFRS implementation, and corporate governance.